'I have a feeling I can't speak to anybody': A thematic analysis of communication perspectives in people with Huntington's disease. (March 2019) - Zarotti, Nicolò; Simpson, Jane; Fletcher, Ian
Objectives: This study explored the perspectives of people affected by Huntington's disease (HD) on their own communicative abilities. Methods: Qualitative semi-structured interviews were carried out with eight people with early HD. The data were analysed through thematic analysis. Results: Four themes were constructed from the data, characterised by the following core topics: How HD directs and mediates communication; Regaining control to improve communication; Emotional outflows into communication and the struggle for separation; Sheltering as a way to boost confidence in communication. Discussion: Separating patients' identity as individuals from that of a person with a disease can help increase communicative control. Consistent with the general theory and model of self-regulation, patients should be allowed a wider range of choices to regain control over communication. Achieving better emotion regulation is of paramount importance for communication, and factors such as medication regimes, relationships and existing coping strategies should be strengthened. Consistent with previous research, feelings of safety and the idea of a safe place ('sheltering') represent an effective coping mechanism. Practical implications include the refinement of communication and relationships among clinicians, caregivers, and patients with HD by considering a wider range of medical, psychological and socio-environmental factors.